Global, regional and national burden and time trends of malaria in children and young adolescents under 15 years from 1990 to 2021: a worldwide observational study - Qiao Liu; Shimo Zhang; Yu Wu; Weijing Shang; Min Liu; Jue Liu (BMC Infectious Diseases)
Abstract Background The global burden of malaria among children remains severe; however, there is a dearth of comprehensive studies comparing this burden across different countries and regions. This study aims to analyze the patterns and trends in malaria burden among children under the age of 15 at global, regional, and national levels from 1990 to 2021, and to investigate the correlation between malaria burden and the developmental status of different countries. Methods This observational study utilized data from the Global Burden of Diseases Study to examine incidence and mortality rates of malaria in children under 15 between 1990 and 2021. The rates and absolute number of malaria cases and deaths showed the epidemic status of malaria. The estimated annual percentage change (EAPC) quantified the time trends of malaria burden. Nonlinear regression was conducted to explore the association between the Socio-demographic Index (SDI) and rates across countries from 1990 to 2021. Results In 2021, there were 169,052,260 malaria cases and 469,881 deaths among children under 15 worldwide, with an incidence rate of 8402.78 per 100,000 and a mortality rate of 23.36 per 100,000. From 1990 to 2021, the global incidence rate of malaria in children under 15 showed a slight increase of 0.87% annually from 2015 to 2021, while the mortality rate decreased by 0.69% per year from 1990 to 2015 but remained stable thereafter. Additionally, there was a notable increase in the number of deaths and mortality rate from malaria in 2020 and 2021 compared to 2019. The most affected regions were in Sub-Saharan Africa, with Western, Eastern, and Central regions having the highest number of cases and deaths. Analysis by SDI indicated that low SDI regions experienced the highest burden of malaria, although all regions saw the highest incidence and mortality rates in children under 5. Despite improvements in mortality rates from 1990 to 2015, some regions such as Oceania, the Caribbean, Tropical Latin America, and North Africa and the Middle East observed increasing trends in incidence rates post-2015. Conclusion Improving socio-economic conditions is urgently needed to alleviate malaria-related morbidity and mortality among children. Our results highlight the need for targeted national policies and stronger international cooperation, especially in regions with low SDI and significant disparities. With concerted efforts, we can significantly reduce malaria’s impact and move closer to a malaria-free world.